2021
DOI: 10.22246/jikm.2021.42.6.1255
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Patients Visiting Department of Korean Internal Medicine in a Korean Medicine Hospital Before and During COVID-19 - From July 2018 to June 2021 at Wonkwang University Jeonju Korean Medicine Hospital -

Abstract: Objectives: This study aimed to analyze the healthcare utilization behavior of patients visiting the department of Korean internal medicine in the Korean medicine hospital of Wonkwang University in Jeon-ju from July 2018 to June 2021.Methods: We retrospectively analyzed the medical records of 26,108 patients and sorted the data by period, month, visiting types, new or returning types, sex, and age group. IBM SPSS 26.0 and the R 4.05 ‘changepoint' package were used with various statistical methods, such as Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…These results are consistent with the findings of a previous study that showed that the medical utilization rate among those under the age of 18 and those in their 20s-40s decreased significantly during the COVID-19 pandemic, while the rate of medical utilization rate among those aged 60 and older slightly decreased [32]. This result can be attributed to several complex factors, such as the tendency of older adults to maintain medical care utilization despite the pandemic, underestimation of subjective health conditions, and increase in the number of the population aged over 65 years every year [22,33].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results are consistent with the findings of a previous study that showed that the medical utilization rate among those under the age of 18 and those in their 20s-40s decreased significantly during the COVID-19 pandemic, while the rate of medical utilization rate among those aged 60 and older slightly decreased [32]. This result can be attributed to several complex factors, such as the tendency of older adults to maintain medical care utilization despite the pandemic, underestimation of subjective health conditions, and increase in the number of the population aged over 65 years every year [22,33].…”
Section: Discussionmentioning
confidence: 98%
“…The Korea Institute of Oriental Medicine published the results of its survey titled "Utilization of Korean Medicine and Consumption of Korean Medicine" in 2020 [20]. Several studies reported the trends of patients visiting Korean Medicine hospitals before and during the COVID-19 pandemic [21][22][23]. However, as far as we know, no previous study has investigated patients visiting a Korean Medicine hospital for a single disease, including facial palsy.…”
Section: Introductionmentioning
confidence: 99%
“…This JAR result is consistent with the results of a previous study showing that the use of medical services by those aged ≤ 18 years and those in their 20s-40s decreased significantly during the COVID-19 pandemic, whereas the utilization rate of patients aged ≥ 60 years decreased slightly [32]. This result can be attributed to several complex factors, such as the tendency of older adults to maintain medical care use despite the pandemic, underestimation of subjective health conditions, and an increase in the population aged > 65 years every year [22,33].…”
Section: Discussionmentioning
confidence: 99%
“…The Korea Institute of Oriental Medicine published the results of its survey titled "Utilization of Korean Medicine and Consumption of Korean Medicine" in 2020 [20]. Several studies reported the trends of patients visiting Korean medicine hospitals before and during the COVID-19 pandemic [21][22][23]. However, to the best of our knowledge, no previous study has investigated patients visiting a Korean medicine hospital for a single disease, including facial palsy.…”
Section: Introductionmentioning
confidence: 99%